A Study of One-Way Road Implementation To Improve Performance In The City of Pagar Alam - Metha Yulinda Eka Putri; Langas Denny Siahaan; Abdullah Ade Suryobuwono (Dinasti International Journal of Digital Business Management, 2024)
This study aims to improve the traffic performance of Major Ruslan Street in Pagar Alam City by implementing a one-way system. The context of this research is the congestion problem caused by secondary obstacles such as illegal, unscheduled loading and unloading and the presence of street vendors that reduce the effective width of the road. This research focuses on the Major Ruslan Road section, which is part of the Central Business District (CBD) area of Pagar Alam City. This study used the VISSIM analysis method to simulate traffic conditions before and after implementing the one-way system. The data was collected through field surveys, including speed, parking, and pedestrian volume surveys. The results show that implementing a one-way system can increase traffic, reduce traffic congestion, and improve road service. In conclusion, implementing effective structured traffic management, such as the one-way system, can be an essential solution to overcome traffic problems in urban areas, especially in Mayor Ruslan Street. This research recommends that the Government of Pagar Alam consider implementing a one-way system as part of more traffic management efforts to improve travel convenience and efficiency.